AN ANALYSIS OF FILM TRANSLATION: A CASE STUDY OF THE FILM "THIS IS THE END" BY SETH ROGEN AND EVAN GOLDBERG - Agista, Dyah Debita (2016)
The title of this research is "An analysis of film translation: A case study of the film 'This Is the End' by Seth Rogen and Evan Goldberg". This research analyzes kind of translation strategies made by Henrik Gottlieb as a great translator, which use in Rogen's film, in film industry it called subtitling. This research used a qualitative research method, especially textual analysis to present the data from the film subtitle. The writer used the entire subtitle from "This Is the End" film. This method allows the writer to make a systematic and detail description of the data with an accurate result. In the process of analyzing the data, the writer conducted several steps. The first step is watching the film with the writer's friend and ask their vote to find out whether the film is funny or not, and to find out their rating on the taboos in the film. The final score of understanding level is 100, humor level gets 82.5 and 47 for taboos and slangs level, which means the subtitle is received by viewers very well and even able to reduce the taboos that were occurred in the original script. After that, the writer analyzed each subtitle to find out the translation strategies. The subtitles were categorized based on the translation strategies as proposed by Henrik Gottlieb (1992). From the whole data that have been analyzed, the translation strategies found aretransfer (480 items or 21.74%), transcription (123 items or 5.57%), paraphrase (661 items or 29.94%), imitation (62 items or 2.81%), dislocation (34 items or 1.54%), expansion (162 items or 7.34%), condensation (513 items or 23.23%), decimation (64 items or 2.90%), deletion (84 items or 3.80%) and resignation (25 items or 1.13%). The findings of this study indicate thatthe most applied strategy is paraphrase, and the least applied strategy is resignation.;-- Judul penelitian ini adalah "An analysis of film translation: A case study of the film 'This Is the End' by Seth Rogen and Evan Goldberg". Penelitian ini menganalisis jenis strategi terjemahan yang dibuat oleh Henrik Gottlieb sebagai penerjemah besar, yang digunakan dalam film Rogen. Dalam industri film ini disebut subtitling. Penelitian ini menggunakan metode penelitian kualitatif, terutama analisis tekstual yang menyajikan data dari subtitle film tersebut.. Penulis menggunakan seluruh subtitle dari film 'This Is the End'. Metode ini memungkinkan penulis untuk membuat deskripsi secara sistematis dan data yang rinci dengan hasil yang akurat. Dalam proses menganalisis data, penulis melakukan beberapa langkah. Langkah pertama adalah menonton film dengan teman-teman penulis dan meminta voting mereka untuk mengetahui apakah film ini lucu atau tidak, dan untuk mengetahui rating mereka pada kata-kata tabu yang terdapat di dalam film. Skor akhir tingkat pemahaman adalah 100, tingkat humor mendapat 82,5 dan 47 untuk tingkat kata-kata tabu, yang berarti subtitle tersebut diterima oleh pemirsa dengan sangat baik dan bahkan mampu mengurangi kata-kata tabu yang terjadi dalam naskah aslinya. Setelah itu, penulis menganalisis setiap subtitle untuk mengetahui strategi penerjemahan. Subtitle dikategorikan berdasarkan strategi penerjemahan yang diusulkan oleh Henrik Gottlieb (1992). Dari seluruh data yang telah dianalisis, strategi penerjemahan yang ditemukan adalah transfer (480 kalimat atau 21.74%), transcription (123 kalimat atau 5.57%), paraphrase (661 kalimat atau 29.94%), imitation (62 kalimat atau 2.81%), dislocation (34 kalimat atau 1.54%), expansion (162 kalimat atau 7.34%), condensation (513 kalimat atau 23.23%), decimation (64 kalimat atau 2.90%), deletion (84 kalimat atau 3.80%) dan resignation (25 kalimat atau 1.13%). Temuan penelitian ini menunjukkan bahwa strategi yang paling banyak diterapkan adalah paraphrase, dan strategi yang paling sedikit diterapkan adalah resignation.